A COMPARATIVE ANALYSIS WAS CONDUCTED TO ASSESS THE IMPACT OF EPIDURAL ADMINISTRATION OF LEVOBUPIVACAINE 0.5% AT A VOLUME OF 20 ML AND ROPIVACAINE 0.75% AT THE SAME VOLUME IN SURGICAL PROCEDURES INVOLVING THE LOWER LIMBS- A PROSPECTIVE STUDY. - Ranjita Mohanty (Student's Journal of Health Research, 2023)
Introduction: The emergence of levobupivacaine and ropivacaine has marked a new phase in advanced pain management techniques. This study aimed to create a comparative framework and assess the effects of epidural levobupivacaine and ropivacaine in surgeries of the lower limb. Methodology: The study involved 100 patients, evenly split into two different groups where each group was assigned 50 candidates. The assignment of patients to these groups was carried out randomly using a lottery-based approach. In Group Levo (n=50), patients were administered 20 ml of 0.5% Levobupivacaine via the epidural pathway, whereas in Group Ropi (n=50), 20 ml of 0.75% Ropivacaine was administered through the same route. Results: The time it took for the sensory block to begin was measured hinged on the completion of the injection until the patient no longer perceived the pinprick sensation. The mean of the onset of time of sensory block reaching up to the T10 level was 12.04 ± 2.71 minutes in group Levo and 11.13 ± 3.10 minutes in group Ropi. Nonetheless, this variation was determined to significantly lack statistical aspects. Conclusion: The results of our study indicated that both drugs exhibited similarities in sensory block attributes. These attributes include the average time it took for sensory blockade to begin and the duration until the highest sensory point was reached. Recommendation: During follow-up and discharge planning, limbs should be checked for numbness and/or weakness, and the patient should be asked about urine retention or headache. Usual medication can be resumed on the day of the procedure. If there is significant limb weakness, sensory loss, or headache, an unplanned overnight admission may be necessary.